Trilemma or Dilemma : Inspecting the Heterogeneous Response of Local Currency Interest Rates to Foreign Rates - Ricci, Luca (IMF Working Papers; Working Paper ;, 2016)
This paper studies the heterogeneous response across countries of local currency interest rates to foreign and domestic factors, thus contributing to the discussion on the policy trilemma in international economics. On average, floaters appear to be less affected by the U.S. in the short run (up to about one year). However, there is large cross-country heterogeneity in the response: floaters that care less about domestic objectives, exhibit stronger fear of floating, or show higher co-cyclicality with the U.S., respond more to foreign rates. This suggests that floating does not necessarily imply a lack of response of local policy rates to foreign ones, but seems to allow independence when needed. Moreover, the effect of foreign rates on the short end of the local interest rate curve seems to operate mainly via the foreign influence on local policy rates, thus suggesting that central banks may be themselves the source of conduit of the 'global credit cycle' discussed by Rey (2014). At the same time, most countries face the equivalent of a 'Greenspan conundrum' as their long term rates are mainly influenced by foreign factors.